The Role of PDK and PUK in the Formation of Parliament and Government Cabinet Between (1992-2006) (Raparin Journal of Humanities (RJH), 2021)
In 1992, for the first time, the Kurdistan region of Iraq went through political and societal change like the formation of parliament and government cabinet. This research is a theoretical one on the role of PDK and PUK in the building of parliament and government cabinet between (1992-2006). This research analyses the role of the both parties in the formation of the parliament in 1992 and 2005, and the government cabinet from the first to fifth. Additionally, this research focuses on the division of power between the two parties during (1992-2005) then the research concluded by the main findings such as, the Role of the both parties in the building of parliament and the government cabinet from the first two the fifth in the region and sharing power in the (1,2,5) government cabinets.